TRANSLATING ENGLISH TEXTS THROUGH AI: LIMITATIONS AND ADVANTAGES - Rakhimova Gavkhar Jamshid kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article examines the evolving role of Artificial Intelligence (AI) in the translation of English written texts, highlighting both its transformative potential and its inherent limitations. Rapid advances in neural machine translation (NMT) and natural language processing (NLP) have made AI tools faster, more accessible, and increasingly accurate. Nevertheless, challenges persist in cultural interpretation, stylistic adaptation, and data security. Through a comprehensive analysis of the advantages and constraints of AI-assisted translation, this study argues that the most effective approach involves a collaborative model integrating both AI and human expertise. The findings underline the need for continued research into improving contextual understanding, ethical use, and multilingual inclusion in AI translation technologies.